Outcome of children of parents with atopic asthma and transient childhood wheezy bronchitis. Issue 11 (November 1997) - Christie, G L; Helms, P J; Ross, S J; Godden, D J; Friend, J A; Legge, J S; Haites, N E; Douglas, J G
Abstract : BACKGROUND: Childhood asthma and wheeze only in the presence of respiratory infection (wheezy bronchitis) appear to have different prognoses and may differ in their aetiology and heritability. In particular, slight reductions in lung function may be associated with episodes of wheezing associated with intercurrent viral infection. METHODS: Outcomes for wheezing symptoms and lung function were studied in 133 offspring of three distinct groups of 69 middle aged probands with childhood histories of (1) atopic asthma (n = 18), (2) wheeze associated with upper respiratory tract infection (wheezy bronchitis, n = 24), and (3) no symptoms (n = 27). Probands were selected from a previously studied cohort in which outcomes of wheezy bronchitis and asthma had been shown to differ. RESULTS: Children of probands with wheezy bronchitis had a lower prevalence of current wheezing symptoms. Forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) in boys of probands with a history of wheezy bronchitis were significantly reduced compared with either of the other two groups (p < 0.0001). In a multivariate analysis, grouping based on parent proband had a significant effect on lung function, independent of factors such as symptoms, atopy or smoking history. CONCLUSIONS: The different symptomatic and lung function outcome in children of probands with wheezy bronchitis and asthma provides further evidence that wheezy bronchitis and asthma differ in their natural history and heritability, and suggests that there may be familial factors specific to each wheezing syndrome.